An efficient regional ionospheric model using combined GPS/BeiDou observations. Issue 2 (3rd July 2017) - Abdelazeem, Mohamed; Çelik, Rahmi N.; El-Rabbany, Ahmed
Abstract: In this study, we develop a regional ionospheric model (RIM) based on the GPS-only observations and the combined GPS/BeiDou observations for single-frequency precise point positioning (SF-PPP) users in Europe. GPS/BeiDou observations from 16 reference stations are processed in the zero-differenced mode. A least-squares algorithm is developed to determine the total electron content (TEC) bi-linear function parameters for a 15-min time interval. The inverse distance weighted (IDW) interpolation technique is used to create the vertical TEC maps for a 1° × 1° grid. The developed models are evaluated for PPP applications using GNSS observations from another set of reference stations. The SF-PPP accuracy and convergence time obtained through the RIMs are assessed and compared with those obtained through the International GNSS Service Global Ionospheric Maps (IGS-GIM). The results show that the RIMs accelerate the convergence time and improve the positioning accuracy in the horizontal and height components in comparison with the IGS-GIM counterparts.